(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Santosa S, Sutarno, Purwanto E, Suranto, Sajidan. 2018. Molecular characterization of Plant Growth Promoting Rhizobacteria using 16S rRNA sequences in the organic rice field of Sukorejo Village, Central Java, Indonesia. Biodiversitas 19: 2157-2162. Plant Growth Promoting Rhizobacteria (PGPR) are rhizosphere bacteria that can be utilized to increase plant growth and suppress plant diseases. PGPR concentrate on the concept of sustainable agriculture due to their role as biostimulant by synthesizing and regulating the concentration of various phytohormones and as biofertilizers. It is important to determine the original PGPR found in the roots of rice plants. This study aimed to identify PGPR based on 16S rRNA sequences. The bacterial strain was isolated from the rhizospheric soil of IR 64 organic and inorganic rice fields in the region of Sragen District, Central Java, Indonesia. The bacterial isolates were grown on the Luria Bertani (LB) Agar Medium. There were 10 colonies obtained with different morphological variations, nine of those were from the organic rice field. Molecular characterization using 16R rRNA sequences suggested the identity the nine isolates were of Pseudomonas aeruginosa strain RI-98-1, Stenotrophomonas maltophilia strain S431, Bacillus subtilis strain CEB2, Bacillus cereus strain ATCC 14579 clone EA195, S. maltophilia strain 5517, Exiguobacterium acetylicum strain SSA-3, Serratia nematodiphila strain HC4, Bacillus cereus strain ANP221, and Acinetobacter junii strain M. pstv. 21.4 Pseudomonas and Bassilus produce phytohormones (auxins) and convert inorganic phosphate to organic and Stenotropomonas can increase the growth of Acinetobacter and Exigobacterium as phosphate solvents in the soil.